The State’s Strategy to Strengthen the Russian Macropolitical Identity in the Digital Space: Dynamics and Prospects - Andrey N. Iokhim (RUDN Journal of Political Science)
Identifying the dynamics and prospects of the state’s communication strategy in the digital space, aimed at strengthening and increasing the stability of the Russian macropolitical identity is in the focus of major research project and this study as it’s part. To achieve this goal, the study identifies threats and risks to the sustainability of macropolitical identity in the digital space, due to both the very specifics of the functioning of the digital environment and the actual realities of the global information and cognitive confrontation in which the Russian state is today. The dynamics of the transformation of the structure of digital communications and digital media consumption of Russians in the last two years, as well as the role and place occupied by the problem of macropolitical identity in this structure is to be discussed. The promising approaches to building an effective strategy of the state to ensure the sustainability of the Russian macropolitical identity are offered.